2017
DOI: 10.1530/erc-17-0187
|View full text |Cite
|
Sign up to set email alerts
|

Role of chromosomal instability in cancer progression

Abstract: Cancer cells often display chromosomal instability (CIN), a defect that involves loss or rearrangement of the cell's genetic material -chromosomes -during cell division. This process results in the generation of aneuploidy, a deviation from the haploid number of chromosomes, and structural alterations of chromosomes in over 90% of solid tumours and many haematological cancers. This trait is unique to cancer cells as normal cells in the body generally strictly maintain the correct number and structure of chromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 92 publications
(99 reference statements)
2
67
0
Order By: Relevance
“…The latter patient harbored five high level of DNA coamplifications that may have a synergistic effect and be deleterious for NB cell survival, considering that this case was the only one in complete remission. It is known that elevated chromosomal instability (CIN) may surpass the threshold compatible with cell viability of tumor cells . Paradoxically, high level of CIN in cancer has been shown to impact survival outcome and with therapeutic responses improving prognosis, due to the excess of genotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…The latter patient harbored five high level of DNA coamplifications that may have a synergistic effect and be deleterious for NB cell survival, considering that this case was the only one in complete remission. It is known that elevated chromosomal instability (CIN) may surpass the threshold compatible with cell viability of tumor cells . Paradoxically, high level of CIN in cancer has been shown to impact survival outcome and with therapeutic responses improving prognosis, due to the excess of genotoxicity .…”
Section: Discussionmentioning
confidence: 99%
“…CIN as a prognostic tool CIN is commonly associated with tumorigenesis and clinical outcomes ( Supplementary Table S1); various reports have shown that aneuploidy that arises as a consequence of CIN in malignant tumors favors the evolution of tumors (88)(89)(90). Investigation of CIN signatures from specific genes whose expression was consistently associated with total functional aneuploidy in many different cancer types and the net overexpression of this signature were predictive of poor clinical outcome in 12 cancer data sets representing 6 cancer types (91).…”
Section: Future Perspectives Of Cinmentioning
confidence: 99%
“…Aneuploidy -deviation from a multiple of the haploid chromosome number -is the leading cause of spontaneous miscarriage and birth defects in humans (Nagaoka et al, 2012) and represents a key hallmark of cancer (Mitelman) where recurrent patterns of aneuploidy, or somatic copy number alteration (SCNA) are observed (Ben-David et al, 2016;Duijf et al, 2013;Faggioli et al, 2012;Mitelman;Nagaoka et al, 2012). SCNA patterns in cancer are a consequence of 'chromosome alteration' rate driven by chromosomal instability (CIN), which is associated with poor prognosis for cancer patients Jamal-Hanjani et al, 2015;Laughney et al, 2015;Lee et al, 2011;McClelland, 2017) coupled to evolutionary selection. Human chromosomes vary widely in size, gene density, interphase nuclear territory and heterochromatin distribution (Figure 1a, Table S1).…”
Section: Introductionmentioning
confidence: 99%